Platonia insignis Mart: Caracterização Química e efeito antimicrobiano em bactérias causadoras de sepse. - FRANCO, Danielle Cristine Gomes (2022)
Sepsis is a public health problem, as it causes physiological, pathological, and biochemical abnormalities as a result of an association between the infection and the uncontrolled systemic inflammation. Thus, the search for new treatments is always necessary, and the natural products are the most promising alternatives, including, the plant species Platonia insignis Mart. The various parts of P. insignis have different biological activities, but there are few studies using the leaves. Thus, our aim was to chemically characterize the hydroethanolic extract of P. insignis Mart leaves (EHPI) and to evaluate its toxicity and its antibacterial effect in vitro and in vivo. The EHPI was chemically characterized by (HPLC-DAD) and (LC-ESI/MS). Toxicity was evaluated in vitro using sheep erythrocytes and in vivo on Tenebrio molitor larvae. The antibacterial sensitivity profile was determined by Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), using standard samples of Gram-positive bacteria [Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 29212), S. pneumoniae (ATCC 49619)] and Gram-negative [Escherichia coli (ATCC 35218), Pseudomonas aeruginosa (ATCC 27853), Klebsiella pneumoniae (ATCC 700603)]. The EHPI in vivo action was determined in Tenebrio molitor larvae lethally infected with Enterococcus faecalis or Escherichia coli (1.5 × 108 CFU/ mL) and in mice to a polymicrobial sepsis cecal perforation and ligation (CLP) method. The major compounds identified were Quinic Acid, Vitexin, Orientin, Ononine, Fukugentin, Fukugentin Dimer and Procyanidin Dimer. Hemolytic activity for sheep erythrocytes was less than 3% for the three lowest concentrations (1 mg/mL: 0.257% and 5 mg/mL: 2.079% and 10 mg/mL: 2.075%) and was 11% for the highest concentration (50 mg/kg). The low toxicity of the extract was also confirmed in vivo after treatment of T. molitor larvae with the same doses, but in this assay the highest concentration (50mg/mL) was toxic to the larvae. The extract showed in vitro antimicrobial activity for all strains tested, but was more effective for E. faecalis (0.19 ± 0.17) and E. coli (0.25 ± 0.11). The treatment with EHPI reduced the growth curve and decreased the viability of E. faecalis (ATCC 29212) or E. coli (ATCC 35218) biofilms. The infected and untreated larvae died within 72 hours, while the treatment with EHPI prolonged the survival of all animals lethally infected with E. faecalis (ATCC 29212) or E. coli (ATCC 35218), in a dose-dependent manner. and with similar efficacy to Meropenem. EHPI was also able to improve the survival mice submitted to lethal Sepsis by CLP, when compared to the other groups. In conclusion EHPI improved the survival during experimental sepsis due to the presence of bioactive compounds with antimicrobial activity, and direct action on bacterial growth, which allows classifying the EHPI as an important target in the bioprospecting of products with antibacterial activity.